Three-Dimensional versus two- dimensional Radiographic Analysis of Alveolar Bone Dimensions and Maxillofacial Landmarks: A Comparative Evaluation for Precision Treatment Planning - Upadhyay, Preeti; Kaur, Manpreet; Mittel, Manika; Kumar, S.; Panwar, Deepanshu; Pandit, Ashish (Journal of Neonatal Surgery, 2025)
Background: Dental radiography is essential for diagnosing oral and maxillofacial conditions. Panoramic radiography (OPG) offers a cost-effective two-dimensional view suitable for routine assessments, while cone-beam computed tomography (CBCT) provides three-dimensional imaging, ideal for complex cases like implant planning and surgical precision. Although OPG is quick and low in radiation, it has spatial inaccuracies, making CBCT preferable for advanced diagnostics. Evaluating OPG's magnification factor is vital for accurate diagnoses. Methods: Seventy-five patients at Inderprastha Dental College and Hospital with clear OPG and CBCT images of maxillary and mandibular landmarks were included. Only patients without jaw pathologies and with healthy periodontal conditions were selected. Vertical and horizontal distances from key anatomical sites were measured, with CBCT used as the reference. Statistical analyses validated the results. Results: OPG measurements of alveolar bone dimensions were comparable to CBCT, showing a strong positive correlation (r = 0.924 to 0.994; p < 0.001). Minor accuracy discrepancies were noted in complex regions, although statistically insignificant. These variations may be relevant in high-precision cases like implant placement. CBCT’s three-dimensional imaging provides superior insights into critical spatial relationships. Conclusion: OPG is reliable for routine alveolar bone measurements, but slight variations in complex areas can affect precision. While OPG is effective for preliminary assessments, CBCT offers enhanced accuracy for intricate cases, such as surgical procedures.